Aqueous Solution Thermal Conductivity of Beryllium-Subgroup Metal Chlorides - K. M. Abdullayev; V. S. Eldarov; R. K. Kerimova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents experimental data on thermal conductivity of BeCl2 and SrCl2 salt aqueous solutions in the temperature range from 20 to 300 °С  and at various electrolyte concentrations  in mass percent. For the first time thermal conductivity of the system Н2О + BeCl2 has been investigated at high temperatures.The experimental results are described with the help of an empirical equation in the form of: λs = λo (1+ Am + Bm3/2 + Cm2),where λs  and λo – thermal conductivity coefficients of solution and water; A, B and C – coefficients depending on electrolyte nature; m – molality in units mol/kg.The formula error is less than  ±1 %.